أثر استخدام استراتيجية التعلم التعاوني على تحسين تحصيل طلبة الصف التاسع في مبحث التربية الفنية - العتوم، منذر سامح محمد (جامعة النجاح الوطنية, 2015)
هدفت الدراسة الحالية إلى التعرف إلى أثر استخدام استراتيجية التعلم التعاوني على تحسين تحصيل الطلبة في مبحث التربية الفنية، وقد أجريت الدراسة على طلبة الصف التاسع في المدارس الحكومية في محافظة (قصبة) المفرق من العام الدراسي 2012/ 2013 م، واستخدم الباحث في دراسته المنهج التجريبي بوجود مجموعة ضابطة وأخرى تجريبية ولتحقيق أغراض الدراسة أعد الباحث قائمة وبطاقة رصد لتقويم أعمال الطلبة. تكون مجتمع الدراسة من جميع طلبة الصف التاسع في مديرية قصبة المفرق، وتم تحديد مدرستين واحدة للذكور وأخرى للإناث، بحيث تحتوي كل مدرسة على شعبتين من طلبة الصف التاسع واحدة منها ضابطة والأخرى تجريبية، وقد تم عشوائيا اختيار (60) طالبا وطالبة من الشعب الأربعة وفق المجموعة والجنس، وقد أظهرت النتائج بعد تحليلها إحصائيا إلى أن هناك فروقا ذات دلالة إحصائية عند مستوى الدلالة بين المجموعة الضابطة والمجموعة التجريبية لتحميل الطلبة، وكانت الفروق لصالح المجموعة التجريبية، وبهذا تبين أن طريقة التعلم التعاوني كانت ذات أثر فاعل في زيادة تحصيل الطلبة، وفي إنماء وتطوير المهارات الفنية لديهم قد يعزي لفاعلية هذه الطريقة في إتاحة الفرصة لمشاركة جميع الطلبة ضمن المجموعة الواحدة عكس الطريقة التقليدية، كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية (α=0.05) تعزى لمتغير الجنس، كذلك أظهرت النتائج وجود فروق ذات دلالة إحصائية (α=0.05) تعزى لمتغيري الطريقة والجنس والتفاعل بينهما، وقدم الباحث العديد من التوصيات أهنها؛ إجراء المزيد من الدراسات باستخدام استراتيجية التعلم التعاوني على متغيرات جديدة كالإبداع الفني والتربية الجمالية والتذوق الفني وعلى عينات ومراحل دراسية مختلفة، وإجراء دراسات أخرى جديدة بتصميمات وأدوات قياس مختلفة عن تلك التي اعتمدت في الدراسة الحالية، ودعوة معلمي التربية الفنية إلى استخدام استراتيجيات التعلم التعاوني، وتطبيق استراتيجية التعلم التعاوني على مباحث دراسية أخرى وصفوف أخرى.
The study aims to investigate the effect of using collaboration learning on development the nine grade student's achievements in Art Education. The study was conducted for 9th graders in public schools in Al-Mafraq Government in 2012\2013. The researcher used the experimental approach based on control and experimental groups. To achieve the objective of the study, a checklist was used to asses students' work. then compared it with traditional method. Two schools, one for male and other for female, two schools were identified, each containing two sections of 9th grade (Experimental and control in each). The sample of the study was chosen randomly and totaled (60) male and female students from four classes according to group and gender. The appropriate statistical procedures were performed on the collected data The study showed that there is statistically significant differences due to the teaching method used, in favor of experimental group students and this shows that collaboration learning method has an effective effect in increasing students' achievement and has a positive effect in developing students' technical skills. The effectiveness of this method contributed in increasing the opportunity to participate of all students within the experimental group compared to the traditional method. The study results also showed that there are statistically significant differences at (α=0.05) contributes due to gender, and the results showed that there are statistically significant differences at (α=0.05) due to the teaching method and the interaction between teaching method and gender. Based on these results, the study recommended that future research may examine the use of collaboration learning strategy on developing other skills such as creativity, aesthetic education and art taste. The study also recommended the use of other research designs, different instruments for data collection and to encourage teachers to use collaborative learning strategy in other school subjects.
Keywords: الاستراتيجيات التعليمية -- التعلم التعاوني -- التحصيل الدراسى -- التربية الفنية